2012
DOI: 10.1007/s00128-012-0648-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) Reduction by Cell Free Extract of Ochrobactrum anthropi Isolated from Tannery Effluent

Abstract: Chromium-resistant bacteria isolated from industrial wastes can be used to detoxify toxic chromium from contaminated sources. From effluent of Shafiq Tannery, Kasur, Pakistan, bacterial strain STCr-1 that could endure 40 mg mL(-1) of potassium chromate in nutrient agar medium was isolated. STCr-1, identified as Ochrobactrum anthropi by 16S rRNA gene sequence homology, demonstrated substantial Cr(VI) reduction at pH 7 and temperature 37°C. It completely reduced 250 μg mL(-1) of Cr(VI) and showed 71.2 % Cr(VI) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…However, the psychrophilic temperature (e.g., 20 °C) was not beneficial to the Cr(VI) removal efficiency of O. anthropi YC152. The optimal pH and temperature for Cr(VI) removal by using O. anthropi observed in this study were consistent with those reported by Sultan and Hasnain (2012) [ 32 ]. Electrolytes, such as Na + and Cl − , exist at a high concentration in wastewater and can potentially affect the activity of microbes and the function of ion-exchange membranes in MFCs [ 23 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the psychrophilic temperature (e.g., 20 °C) was not beneficial to the Cr(VI) removal efficiency of O. anthropi YC152. The optimal pH and temperature for Cr(VI) removal by using O. anthropi observed in this study were consistent with those reported by Sultan and Hasnain (2012) [ 32 ]. Electrolytes, such as Na + and Cl − , exist at a high concentration in wastewater and can potentially affect the activity of microbes and the function of ion-exchange membranes in MFCs [ 23 ].…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, Figure 4 B indicates that the other regression equation was determined to be y = −15.027 x + 156.8 ( r 2 = 0.9914) when the Cr(VI) concentration ranged from 0.3 to 5 mg/L. The different relationships observed in different Cr(VI) concentrations may be because of Cr(VI) reduction rates and bacterial characteristics [ 32 ]. Hence, on the basis of these two equations, the Cr(VI) concentration in the water samples can be rapidly determined using the developed MFC biosensor.…”
Section: Resultsmentioning
confidence: 99%
“…Most of reported Cr(VI)-reducing strains directly enzymatically reduce Cr(VI) to Cr(III) (Camargo et al 2003;Thacker et al 2007;Mistry et al 2010;Chen et al 2012;Focardi et al 2012). Chromate reductase activity is associated with the soluble cell fraction (Pal et al 2005;Sultan and Hasnain 2012) or membrane cell fraction (Wang et al 1990;Mangaiyarkarasi et al 2011). The purified soluble flavoproteins showed the activity of enzymatic Cr(VI) reduction in Pseudomonas putida and Escherichia coli (Ackerley et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…The routine abatement mechanism for chromium pollution generally involves reduction of Cr 6+ to Cr 3+ , and subsequent precipitation of less soluble chromium at or near neutral pH [8]. There are several methods for removal of chromium from the tanning wastewater.…”
Section: +mentioning
confidence: 99%